2012
DOI: 10.1097/shk.0b013e31825b4ed9
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Resuscitation With Lactated Ringer Compared With Ringer Solution After Severe Hemorrhagic Shock in Rats

Abstract: Lactated Ringer (LR) is a widely used resuscitation fluid that is known to mediate beneficial effects on acid-base balance when compared with normal saline. We here compared LR with the more physiological Ringer solution (RS) regarding acid-base status, hemodynamics, survival, and organ injury following fluid resuscitation subsequent to severe hemorrhagic shock. Anesthetized rats were hemorrhaged to a mean arterial blood pressure of 25 to 30 mmHg within 30 min. After 60 min, they were resuscitated with either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 24 publications
1
23
0
1
Order By: Relevance
“…Contrary to recently published results, our group has shown that Ringer-lactate (RL) may mediate toxic effects in rats with severe hemorrhagic shock (mean arterial blood pressure (MAP) 25 to 30 mmHg) [16]. However, whether this effect occurs exclusively in severe hemorrhagic shock remains unclear.…”
Section: Introductionmentioning
confidence: 88%
“…Contrary to recently published results, our group has shown that Ringer-lactate (RL) may mediate toxic effects in rats with severe hemorrhagic shock (mean arterial blood pressure (MAP) 25 to 30 mmHg) [16]. However, whether this effect occurs exclusively in severe hemorrhagic shock remains unclear.…”
Section: Introductionmentioning
confidence: 88%
“…The immunological and metabolic alterations in response to hypoxia contribute to the damage within the microvascular and tubular components of the kidney, which can be seen histologically. In one study following HS, several blood-filled and shrunken glomeruli were present and tubular necrosis was demonstrated by detached basal lamina [42]. Similarly, while models of electrical burns (and associated rhabdomyolysis) may be of benefit in studying AKI, only histological changes (glomerular congestion, proximal tubule degeneration) were shown without evidencing any functional changes [43].…”
Section: Animal Trauma Models Studying Akimentioning
confidence: 95%
“…Renal malondialdehyde generation, reduction in superoxide dismutase (SOD) activity and induction of inducible nitric oxide synthase (iNOS) and subsequent nitric oxide (NO) production were shown after HS in rats [42]. ROS and NOS facilitate the translocation of the transcription factor nuclear factor κ-B (NF-κB) from the cytoplasm to the nucleus, which elicits the inflammatory cascade.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the theory of microcirculation disturbance, fluid resuscitation significantly reduces the morbidity of acute kidney injury (AKI) directly that is induced by ischemia after hemorrhagic shock (2,3). However, the oxidative stress and inflammation response induced by ischemia or reperfusion, hormonal and neural reactions, and vascular hyporeactivity result in refractory hypotension, which consequently causes AKI or acute renal failure (4Y6).…”
Section: Introductionmentioning
confidence: 99%